PREA: A Replication Strategy for Software Deﬁned Storage - Rodrigues , Josino; Garcia , Vinicius; Assad, Rodrigo Elia (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
The Data Storage industry is facing challenges in the management of heterogeneous storage devices, which in most cases, have their own protocols and proprietary management interfaces. Software Deﬁned Storage(SDS) has emerged as a solution to abstract this heterogeneity. Among the existing requirements in a storage system, availability is a requirement that if not met, prevents the use of the storage solution. For some scenarios, performance requirements can be as important as the availability. In such cases, the search for algorithms and eﬃcient strategies for SDS has entered the agenda of not only professionals but also researchers. This work aims to present the PREA, a strategy for data replication in SDS environments focused on availability and performance. The proposed solution takes into account local replication environments, remote replication and hybrid replication (local and remote). This work is in the development stage and in the course of this article will be presenting the advantages, disadvantages, strengths and weaknesses of the proposed approach.